Enhanced current-induced magnetization switching via antiferromagnetic coupled interface in Co/Ho heterostructures - Li, Shaomin (2024)
Rare-earth ferromagnetic (RE-FM) heterostructures have attracted significant attention due to their intricate spin structures and physical phenomena. The antiferromagnetic coupled (AFC) interface formed by the distinctive interaction between the FM and RE elements has critical contributions to the magnetization reversal process. In this work, we investigate the enhancement of current-induced magnetization switching with the AFC interface at the Co/Ho heterostructure. The results shows that an increased spin-orbit torque (SOT) efficiency of up to 250% was achieved at a Ho thickness of 7 nm, with a critical switching current density of 2.7 × 1010 A/m2. When a Cu interlayer was introduced between the Co/Ho interface, a decreased SOT efficiency was observed, indicating that the SOT enhancement is primarily attributed to the AFC interfacial effect. At the AFC interface, the interaction between Co and Ho atoms generates an additional torque, enhancing the effective SOT efficiency.